Potensi Reduksi Gas Rumah Kaca di TPA Kawatuna melalui Proyek Pemulihan Gas Metana: Reduction of Greenhouse Gases in Kawatuna Landfill through Methane Gas Recovery Project - NURUL ANNISA R. NOCH; PINI WIJAYANTI (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2022)
ABSTRACT The Palu City Government plans to reactivate the biogas power plant (PLTBg) project in Kawatuna landfill, which was operated in 2013. Both economic and environmental benefits of the project are important for decision makers. The environmental benefit include the potential reduction of greenhouse gases (GHGs) emissions by the project. The economic benefits are important to estimate as the financial attractiveness of the project, which include the electricity generated and revenue from Certified Emission Reduction (CER). This study aims (1) to estimate the potential GHGs emissions produced by the Kawatuna landfill before PLTBg project, (2) to estimate the potential GHGs emissions reduction due to the project, (3) to calculate the potential CER that can be obtained from the project. This study employs Clean Development mechanism (CDM) AMS-III.G method to estimate the potential GHGs reduction and a simple quantitative analysis to calculate the potential CER of the project. The results show that based on the BAU Scenario in 2021, the estimated baseline GHGs emissions is 16.148,74 t CO2e, the potential GHGs reduction after the project would reach 61,40% of the total GHGs emissions generated and the range of potential CER would be from 28.595.318 IDR to 72.329.334 IDR. From 2021 to 2030, total present value of CER would reach 563.358.389 IDR. Keywords: CDM, CER, GHG Emissions, Kawatuna, PLTBg ABSTRAK Pemerintah Kota Palu berencana menghidupkan kembali proyek pembangkit listrik tenaga biogas (PLTBg) di TPA Kawatuna yang sempat beroperasi pada tahun 2013. Informasi mengenai manfaat yang akan diperoleh dari sudut pandang ekonomi dan lingkungan adalah penting bagi pengambil keputusan. Salah satu manfaat lingkungan yaitu potensi reduksi emisi gas rumah kaca (GRK) oleh proyek PLTBg. Manfaat ekonomi penting untuk diestimasi sebagai daya tarik finansial dari proyek, di antaranya berasal dari nilai potensi energi listrik yang dihasilkan dan penerimaan proyek dari Certified Emission Reduction (CER). Tujuan penelitian ini adalah (1) mengestimasi potensi emisi GRK yang dihasilkan oleh TPA Kawatuna sebelum implementasi proyek pemulihan gas metana, (2) mengestimasi potensi reduksi GRK dari proyek tersebut, (3) menghitung potensi nilai CER yang dapat dihasilkan dari proyek tersebut. Penelitian ini menggunakan metode CDM AMS-III.G untuk mengestimasi potensi reduksi GRK dan menggunakan kuantitatif sederhana untuk mengestimasi nilai CER proyek. Hasil penelitian menunjukkan melalui Skenario BAU pada tahun 2021, potensi emisi GRK sebelum adanya proyek adalah 16,148,74 t CO2e dan potensi reduksi GRK setelah adanya proyek mencapai 61,40% dari total emisi yang dihasilkan. Potensi penerimaan CER proyek pada tahun 2021 berkisar antara Rp 28.595.318 hingga Rp 72.329.334 dan total present value penerimaan CER pada tahun 2021-2030 mencapai Rp 563.358.389. Kata kunci: CDM, CER, Emisi GRK, Kawatuna, PLTBg